From riverscape to energyscape: Constructing the space of hydroelectricity production in the İkizdere River Valley, Turkey. - Eren, Ayşen. (Thesis (Ph.D.) - Bogazici University. Institute of Environmental Sciences, 2017., 2017)
This dissertation examines the processes, relations, and practices by which all the involved parties construct, sustain and contest the space of hydroelectricity production in the İkizdere River Valley, Turkey. Beginning with the first hydroelectricity plant built in 1950s, the İkizdere HES, the study traces historical small-scale hydroelectricity development in the valley, and then focuses on "the sustainable development" of hydroelectricity program launched in 2003. The thesis explores how the program came about on the national scale and materialized on the İkizdere River Valley with the emergence of five private hydroelectricity plants. It also seeks to explain how the emerging hydroelectricity plants have contributed to the deterioration of the once-positive local perception toward hydroelectricity production. Moreover, this thesis focuses on the water-electricity nexus in order to better understand the hydroelectricity development and to demonstrate the real scale of its environmental and social consequences in the valley. The thesis follows an interdisciplinary methodology, integrating multi-sited fieldwork with a mixed-method design. It employs Lefebvre's the theory of space together with the concepts of relations of production and infrastructure in analyzing the processes and relations. In addition, the thesis uses a post-structuralist approach in examining the policies, regulations, and practices constituting hydroelectricity development program.
Keywords: Hydroelectric power plants -- İkizdere (Turkey); Rivers -- Turkey.